USING MICROSOFT IT ACADEMY FOR THE FORMATION OF THE ICT COMPETENCE OF TEACHERS AND STUDENTS - Honcharenko, Tetiana O.; Tiutiunnyk, Anastasiia V. (Educological discourse, 2014)
The main feature of the modern education system is using computer technology, which penetrates into all aspects of society. This article presents an overview of courses the Microsoft IT Academy. The analysis capabilities Microsoft IT Academy, presented in BorysGrinchenko Kiev University. Described how they can be used in the formation of ICT competence of student. Also presents how can use Microsoft IT Academy courses in the study subjects with using information and communication technologies in BorysGrinchenko Kiev University.